2005
DOI: 10.1021/bc050004z
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Sensitization of Liposomes by Use of Thermosensitive Block Copolymers Synthesized by Living Cationic Polymerization:  Effect of Copolymer Chain Length

Abstract: We prepared block copolymers of (2-ethoxy)ethoxyethyl vinyl ether (EOEOVE) and octadecyl vinyl ether (ODVE) with the number average molecular weights of 6900, 9300, and 16 700 by living cationic polymerization. The poly(EOEOVE) block acts as a temperature-sensitive moiety, and the poly(ODVE) block acts as an anchor moiety. We also investigated the effect of chain length of the copolymer poly(EOEOVE) block on the ability to sensitize liposomes. The copolymers underwent a coil-globule transition at approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 33 publications
4
58
0
Order By: Relevance
“…Thus, the fast PS component ( τ 1 ) should become faster still with increasing C , as clearly demonstrated in Figure 5 a. It should be noted here that interchain aggregation even below LCST (meaning before PS) was also discussed for a block copolymer system of poly(EOEOVE) and octadecyl vinyl ether, [ 38 ] reinforcing our deduction where intermolecular aggregates play an important role in PS.…”
Section: Concentration and Molecular Weight Dependence Of Ps Dynamicssupporting
confidence: 83%
“…Thus, the fast PS component ( τ 1 ) should become faster still with increasing C , as clearly demonstrated in Figure 5 a. It should be noted here that interchain aggregation even below LCST (meaning before PS) was also discussed for a block copolymer system of poly(EOEOVE) and octadecyl vinyl ether, [ 38 ] reinforcing our deduction where intermolecular aggregates play an important role in PS.…”
Section: Concentration and Molecular Weight Dependence Of Ps Dynamicssupporting
confidence: 83%
“…Such disagreements between the thermal properties of the bilayers and the anisotropy ratios suggest that the anisotropy ratio is not a function of the bilayer properties but rather represents macroscopic properties of the vesicle, specifically, the vesicle size. This conclusion is supported by the results of Kono et al [32] who found that polymer-associated liposomes with similar vesicle sizes have almost the same membrane fluidity regardless of differences in the molecular weight and concentration of the polymers.…”
Section: Correlations Between Vesicle Size Transition Temperature Asupporting
confidence: 72%
“…Copoly[EOEOVE-block-octadecyl vinylether(ODVE)] was synthesized as previously reported using 1-(ethoxy)ethyl acetate as the initiator [36]. The number average molecular weight and polydispersity index of copoly(EOEOVE-block-ODVE) were estimated to be 1.3x10 4 and 1.03, respectively, using gel permeation chromatograpy.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the highly branched backbone structure with many chain terminals, the dendron moiety taking on a compact conformation can hold many Gd-chelate residues. Based on the highly temperature-responsive liposomes, which were developed recently by modification of pegylated liposomes with thermosensitive poly [2-(2-ethoxy)ethoxyethyl vinyl ether-block-octadecyl vinyl ether (EOEOVE-block-ODVE)] with a lower critical solution temperature (LCST) around 40°C [36,37], we incorporated the dendron-based lipid having many Gd-chelates into the poly(EOEOVE-block-ODVE)-modified liposomes ( Figure 1). Performances of the liposomes from the sense of visualization and tumor-chemotherapy were investigated.…”
Section: Introductionmentioning
confidence: 99%